Hubungan Keukuatan Otot Lengan dan Power Tungkai dengan Kemampuan Jump Shoot Tim Putri Extrakulikuler Bolabasket SMA Negeri 1 Sukaraja Sukabumi - Faiz Faozi; Novy Yuliantini (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2021)
This study aims to determine the relationship of arm muscle strength and leg power with the jump shot ability of the extracurricular women's basketball team. This research is a Non-Experimental study with correlational design.Data collection techniques in this study were tests. The instruments used in this study were push-up tests, vertical jump tests, and ball-to-ring tests with jump shots that were at 5 shot post points with 5x chance to shoot at each post.The results of the analysis showed that: There was a significant relationship between arm muscle strength and jump shoot, significance value 0.001 <0.05, the magnitude of the relationship between arm muscle strength and Jumpshot by 75.3%. (2) There is no significant relationship between leg muscle power and jump shoot in basketball extracurricular women's teams with t count 3.105> t table 2.23, and significance value 0.316 <0.05. (3) There is a significant relationship between arm muscle strength and leg power simultaneously to Jump shoot ability with r = 0.753 and significance = 0.001 with sig F change = 0.004.